An Extramedullary Plasmacytoma of the Nasopharynx : A rare entity (Bangladesh Journal of Medical Science, 2016)
A 64 year old female with no underlying medical illness presented with 3 months history of unilateral nasal blockage and rhinorrhoea. Nasopharyngeal examination revealed a smooth surface mass in the posterior nasal space. Endoscopic biopsy confirmed the mass to be Extramedullary Plasmacytoma. Investigation pertaining to multiple myeloma revealed no evidence of the disease. The mass was excised endoscopically and the patient completed 25 cycles (50Gy) radiotherapy. Patient had no evidence of recurrence after 6 months follow up.Bangladesh Journal of Medical Science Vol.15(3) 2016 p.477-479